Analysis of the Impact of Financial Performance on Stock Returns of Companies in the Property and Real Estate Sector - Corneles, Cherine Octhern; Nelwan, Melinda Lydia (Klabat Accounting Review, 2025)
This study aims to analyze the effect of financial performance on stock returns in property and real estate companies listed on the Indonesia Stock Exchange during the period 2020-2023. Financial performance is measured using return on equity, debt to equity, and total asset turnover. The study uses a purposive sampling method with 60 companies as the sample and a total of 240 observations. The analysis results show that, simultaneously, return on equity, debt to equity, and total asset turnover significantly influence stock returns with a contribution of 6.3%. However, partially, return on equity, debt to equity, and total asset turnover do not show a significant effect on stock returns, except when the regression analysis is conducted separately for companies with positive and negative profits, where debt to equity is found to have a negative effect on stock returns for companies with positive profits. These findings suggest that investors may consider other factors, such as economic conditions, government policies, and specific events, in making in-vestment decisions during the Covid-19 pandemic, rather than relying solely on financial ratio analysis.